New and little known species of the genus Songius (Coleoptera: Staphylinidae: Pselaphinae) in China - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
Two new species of the myrmecophilous genus Songius, S. kiwi new species (from Guangxi, southern China), and S. pseudohlavaci new species (from Hunan, central China), are described and illustrated. Additional collection records for S. lasiuohospes and S. hlavaci, as well as an identification key to the species, are given.